Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage treatments on wheat storage

Abstract: An experiment was conducted in Laboratory for Seed Testing of Agronomy Department, Faculty of Agriculture, Mansoura University, Egypt, from 30 th May, 2015 to 11 th March, 2016 to study the effect of storage periods, packages types and treating wheat grains with natural and chemical materials on storage efficacy seed viability and quality under the environmental conditions of Dakahlia Governorate, Egypt. The experiment was arranged in A Factorial Experiment in Randomized Complete Block Design (RCBD) with four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…The difference in mean 1000-seed weight between the Ziplock bag and Aluminum foil tray treatments was greater at Room temperature (1.0g) than at refrigeration (0.5g). These findings were similar to those of other studies, which had also found that the interaction between storage method and packaging material could have a significant effect on 1000-seed weight (Satasiya et al, 2021;Badawi et al, 2017).…”
Section: Tablesupporting
confidence: 92%
“…The difference in mean 1000-seed weight between the Ziplock bag and Aluminum foil tray treatments was greater at Room temperature (1.0g) than at refrigeration (0.5g). These findings were similar to those of other studies, which had also found that the interaction between storage method and packaging material could have a significant effect on 1000-seed weight (Satasiya et al, 2021;Badawi et al, 2017).…”
Section: Tablesupporting
confidence: 92%